Preparation process of halogen-free flame-retardant solid powder coating
The preparation of halogen-free flame-retardant solid powder coatings through multi-step reaction and combined materials process has solved the problem of insufficient flame retardant and antibacterial effects of existing solid coatings, and achieved good flame retardant and antibacterial properties.
Patent Information
- Application Number
- CN202411263165.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing solid coatings have shortcomings in flame retardant and antibacterial effects, especially the antibacterial effects have not been improved.
A halogen-free flame-retardant solid powder coating is used to produce a cashew phenol-modified phenolic resin through the reaction of phenol, formaldehyde and oxalic acid, and it is used to form a cashew phenol-modified phenolic resin with hydroxy-1-methacryloyloxydamantane and hexamethyldisilicone Azalkane, tertiary amine domandane, quaternized adamantane, adamantane modified phenolic resin, L-cysteine modified carbon nanotubes and other materials carry out multi-step reaction, combining vinyl carbon nanotubes and talc powder, Halogen-free flame-retardant solid powder coatings are produced by screw extruder and grinding processes.
Achieve good flame retardant and antibacterial effects. The existence of silicon and sulfur elements plays flame retardant and heat-absorbing protection respectively. The adamantane structure improves mechanical properties. The cashew phenol groups and quaternary ammonium salts in the phenolic resin are synergistic. Antibacterial, significantly improving the flame retardant and antibacterial properties of the paint.
Smart Images

Figure BDA0005036366300000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, in particular to a preparation process of a halogen-free flame-retardant solid powder coating. Background Art
[0002] Solid coating is a kind of coating of polymer compounds that forms a solid network structure after construction. It has various types and a wide range of applications. It forms a coating film that can no longer be dissolved by solvents or melted by heat through a cross-linking reaction, thereby providing a lasting protection and decorative effect, but its flame retardant and antibacterial effects are not improved. For example, patent CN117229695B discloses a modified high-solid coating and its preparation method, which has a good anti-corrosion effect, but its antibacterial effect is not improved. Summary of the invention
[0003] 1. Technical issues to be resolved
[0004] In view of the deficiencies of the prior art, the present invention provides a preparation process of a halogen-free flame retardant solid powder coating, which has good flame retardant and antibacterial effects.
[0005] (II) Technical solution
[0006] To achieve the above object, the present invention provides the following technical solution: a preparation process of a halogen-free flame retardant solid powder coating, the preparation process of the halogen-free flame retardant solid powder coating comprising the following steps:
[0007] (1) adding an aqueous solution of phenol and formaldehyde and oxalic acid into a three-necked flask, reacting at 60-80° C. for 2-4 hours, then adding cardanol thereto, continuing the reaction for 3-5 hours, washing with deionized water after the reaction, standing for 16-24 hours, filtering and washing after the reaction, and obtaining a cardanol-modified phenolic resin;
[0008] (2) adding 3-hydroxy-1-methacryloyloxyadamantane and hexamethyldisilazane to N,N-dimethylformamide solvent, stirring and dissolving, adding chloroplatinic acid catalyst thereto, reacting at 75-90° C. for 4-8 hours, and then performing reduced pressure distillation, washing and drying to obtain tertiary amine adamantane;
[0009] (3) adding tertiary amine adamantane and p-chloromethylbenzoyl chloride to N,N-dimethylformamide solvent, introducing nitrogen protection, reacting at 70-90° C. for 8-10 hours, and then performing rotary distillation and washing to obtain quaternary ammonium adamantane;
[0010] (4) adding dichloromethane solvent, quaternized adamantane, cardanol-modified phenolic resin, and triethylamine catalyst to a reactor, reacting at 30-50° C. for 8-14 hours, separating by column chromatography after the reaction, and washing with petroleum ether to obtain adamantane-modified phenolic resin;
[0011] (5) Add 5-8 parts by weight of vinyl carbon nanotubes and 4-10 parts by weight of L-cysteine into dimethyl sulfoxide solvent, stir and disperse, introduce nitrogen protection, react at 55-70° C. for 2-4 hours, and then add 320-400 W / m 2 UV irradiation, after the reaction is completed, the solvent is removed by vacuum rotary evaporation to obtain L-cysteine modified carbon nanotubes;
[0012] (6) adding quaternized adamantane and L-cysteine modified carbon nanotubes to N,N-dimethylformamide solvent, stirring and mixing, adding pyridine catalyst, reacting at 75-90° C. for 10-13 h, and then distilling under reduced pressure, filtering and drying to obtain adamantane modified carbon nanotubes;
[0013] (7) 6-12 parts by weight of adamantane-modified phenolic resin, 5-8 parts by weight of adamantane-modified carbon nanotubes, 1-3 parts by weight of talc, 0.6-0.9 parts by weight of film-forming aid propylene glycol, and 0.2-0.3 parts by weight of defoamer BYK088 are added to a high-speed mixer and mixed for 6-10 minutes, and then sent to a screw extruder for melt extrusion. The temperature of the feeding section is 30-45°C, the temperature of the melting section is 80-110°C, and the temperature of the discharging section is 110-170°C. The molten material is pressed into tablets by a tablet press to control the thickness to be 2-5 mm, and then crushed and sent to a grinding mill for pulverization and classification. The fine powder and impurities are separated by a cyclone separator, and the product is separated by a powder sieve to obtain a halogen-free flame retardant solid powder coating.
[0014] Preferably, the mass ratio of phenol, formaldehyde aqueous solution, oxalic acid and cardanol in (1) is 2.2-2.5:1:0.4-0.6:0.7-0.9.
[0015] Preferably, the mass ratio of 3-hydroxy-1-methacryloyloxyadamantane, hexamethyldisilazane and chloroplatinic acid catalyst in (2) is 1:1.2-1.4:0.01-0.03.
[0016] Preferably, the mass ratio of the tertiary amine adamantane to p-chloromethylbenzoyl chloride in (3) is 1.1-1.5:1.
[0017] Preferably, the mass ratio of quaternized adamantane, cardanol-modified phenolic resin and triethylamine catalyst in (4) is 1.4-1.7:1:0.02-0.04.
[0018] Preferably, the mass ratio of quaternized adamantane, L-cysteine modified carbon nanotubes and pyridine catalyst in (6) is 1:0.8-1.5:0.01-0.03.
[0019] (III) Beneficial technical effects
[0020] The invention comprises the following steps: reacting phenol, an aqueous solution of formaldehyde, oxalic acid and cardanol to obtain a cardanol-modified phenolic resin; performing an addition reaction on an alkenyl group in 3-hydroxy-1-methacryloyloxy adamantane and a silicon-hydrogen bond in hexamethyldisilazane to introduce a hydroxyl group and a tertiary amine group, thereby obtaining a tertiary amine adamantane; further reacting the adamantane with p-chloromethylbenzoyl chloride to generate a quaternary ammonium salt group and introducing an acyl chloride group to obtain a quaternized adamantane; further reacting the adamantane with a cardanol-modified phenolic resin to obtain an adamantane-modified phenolic resin; performing an addition reaction on an alkenyl group in a vinyl carbon nanotube and a thiol group in L-cysteine; The invention relates to a method for preparing a halogen-free flame retardant solid powder coating, wherein the halogen-free flame retardant solid powder coating is prepared by mixing the quaternized adamantane with the L-cysteine modified carbon nanotubes, and reacting the quaternized adamantane with the L-cysteine modified carbon nanotubes to obtain the adamantane modified carbon nanotubes; the adamantane modified phenolic resin, the adamantane modified carbon nanotubes, talcum powder, film-forming aid propylene glycol, and defoamer BYK088 into a high-speed mixer and mixed, and then sent to a screw extruder for melt extrusion, feeding, melting, and discharging, and the molten material is tableted by a tablet press, and then sent to a grinder for pulverization and classification after being crushed, and the overfine powder, sundries, etc. are separated by a cyclone separator, and the product is separated by a powder sieve to obtain a halogen-free flame retardant solid powder coating.
[0021] The silicon element in the halogen-free flame-retardant solid powder coating can decompose to produce silicon dioxide or other non-combustible substances, forming an isolation film to prevent oxygen from contacting the combustion material, thereby playing a flame retardant role; the protective layer formed by the sulfur element at high temperature has an endothermic effect, which slows down the combustion rate and thus plays a flame retardant role; the carbon nanotubes themselves also have a good flame retardant effect, and the adamantane structure has good stability, which improves the mechanical properties of the coating. The cardanol group in the adamantane-modified phenolic resin has a good antibacterial effect, and synergistically fights against bacteria with quaternary ammonium salts. In addition, the phenolic resin has a large number of reaction sites, which increases the degree of substitution of the quaternary ammonium salt, making its antibacterial effect better. DETAILED DESCRIPTION
[0022] The preparation process of vinyl carbon nanotubes refers to the journal "Materials Science and Engineering Plastics" Volume 23, Issue 4, "Surface Vinyl Functionalization of Multi-walled Carbon Nanotubes": 0.3g of multi-walled carbon nanotubes were added to 30mL of 98% concentrated sulfuric acid and 10mL of 70% concentrated nitric acid, refluxed at 140°C for 1h, filtered, and washed. 0.1g of the acidified carbon nanotubes obtained were weighed and dispersed in 15mL of acetone and 15mL of chloroform, 2mL of triethylamine and 5mL of acryloyl chloride were added, and the reaction was carried out at 40°C for 24h, and then 10mL of ethanol was added and stirred for 2h, filtered, and washed to obtain vinyl carbon nanotubes.
[0023] Example 1
[0024] (1) adding phenol, an aqueous solution of formaldehyde, and oxalic acid into a three-necked flask, reacting at 60° C. for 2 h, and then continuously adding cardanol thereto, wherein the mass ratio of phenol, the aqueous solution of formaldehyde, oxalic acid, and cardanol is 2.2:1:0.4:0.7, and continuing the reaction for 3 h. After the reaction is completed, washing with deionized water and standing for 16 h, after the reaction is completed, filtering and washing to obtain a cardanol-modified phenolic resin;
[0025] (2) adding 3-hydroxy-1-methacryloyloxyadamantane and hexamethyldisilazane to N,N-dimethylformamide solvent, stirring and dissolving, and continuously adding chloroplatinic acid catalyst thereto, wherein the mass ratio of 3-hydroxy-1-methacryloyloxyadamantane, hexamethyldisilazane, and chloroplatinic acid catalyst is 1:1.2:0.01, reacting at 75° C. for 4 h, and then performing reduced pressure distillation after the reaction, washing, and drying to obtain tertiary amine adamantane;
[0026] (3) adding tertiary amine adamantane and p-chloromethylbenzoyl chloride to N,N-dimethylformamide solvent, wherein the mass ratio of tertiary amine adamantane to p-chloromethylbenzoyl chloride is 1.1:1, introducing nitrogen protection, reacting at 70° C. for 8 h, and then rotary distilling and washing to obtain quaternary ammonium adamantane;
[0027] (4) adding dichloromethane solvent, quaternized adamantane, cardanol-modified phenolic resin, and triethylamine catalyst into a reactor, wherein the mass ratio of quaternized adamantane, cardanol-modified phenolic resin, and triethylamine catalyst is 1.4:1:0.02, reacting at 30° C. for 8 h, separating by column chromatography after the reaction, washing with petroleum ether, and obtaining adamantane-modified phenolic resin;
[0028] (5) Add 5 parts by weight of vinyl carbon nanotubes and 4 parts by weight of L-cysteine into dimethyl sulfoxide solvent, stir and disperse, introduce nitrogen protection, react at 55° C. for 2 h, and then add 320 W / m 2 UV irradiation, after the reaction is completed, the solvent is removed by vacuum rotary evaporation to obtain L-cysteine modified carbon nanotubes;
[0029] (6) adding quaternized adamantane and L-cysteine modified carbon nanotubes to N,N-dimethylformamide solvent, stirring and mixing, adding pyridine catalyst, wherein the mass ratio of quaternized adamantane, L-cysteine modified carbon nanotubes, and pyridine catalyst is 1:0.8:0.01, reacting at 75° C. for 10 h, and then distilling under reduced pressure, filtering and drying to obtain adamantane modified carbon nanotubes;
[0030] (7) 6 parts by weight of adamantane-modified phenolic resin, 5 parts by weight of adamantane-modified carbon nanotubes, 1 part by weight of talc, 0.6 parts by weight of film-forming aid propylene glycol, and 0.2 parts by weight of defoaming agent BYK088 were added to a high-speed mixer and mixed for 6 minutes. The mixture was then sent to a screw extruder for melt extrusion. The temperature of the feeding section was 30° C., the temperature of the melting section was 80° C., and the temperature of the discharging section was 110° C. The molten material was tableted by a tablet press with a thickness controlled at 2 mm. The molten material was then crushed and sent to a grinder for pulverization and grading. The fine powder and impurities were separated by a cyclone separator, and the product was separated by a powder sieve to obtain a halogen-free flame-retardant solid powder coating.
[0031] Example 2
[0032] (1) adding phenol, an aqueous solution of formaldehyde, and oxalic acid into a three-necked flask, reacting at 80° C. for 4 h, and then continuously adding cardanol thereto, wherein the mass ratio of phenol, the aqueous solution of formaldehyde, oxalic acid, and cardanol is 2.5:1:0.6:0.9, and continuing the reaction for 5 h. After the reaction is completed, washing with deionized water and standing for 24 h, after the reaction is completed, filtering and washing to obtain a cardanol-modified phenolic resin;
[0033] (2) adding 3-hydroxy-1-methacryloyloxyadamantane and hexamethyldisilazane to N,N-dimethylformamide solvent, stirring and dissolving, and continuously adding chloroplatinic acid catalyst thereto, wherein the mass ratio of 3-hydroxy-1-methacryloyloxyadamantane, hexamethyldisilazane, and chloroplatinic acid catalyst is 1:1.4:0.03, reacting at 90° C. for 8 h, and then performing reduced pressure distillation after completion, washing, and drying to obtain tertiary amine adamantane;
[0034] (3) adding tertiary amine adamantane and p-chloromethylbenzoyl chloride to N,N-dimethylformamide solvent, wherein the mass ratio of tertiary amine adamantane to p-chloromethylbenzoyl chloride is 1.5:1, introducing nitrogen protection, reacting at 90° C. for 10 h, and then rotary distilling and washing to obtain quaternary ammonium adamantane;
[0035] (4) adding dichloromethane solvent, quaternized adamantane, cardanol-modified phenolic resin, and triethylamine catalyst into a reactor, wherein the mass ratio of quaternized adamantane, cardanol-modified phenolic resin, and triethylamine catalyst is 1.7:1:0.04, reacting at 50° C. for 14 h, separating by column chromatography after the reaction, and washing with petroleum ether to obtain adamantane-modified phenolic resin;
[0036] (5) 8 parts by weight of vinyl carbon nanotubes and 10 parts by weight of L-cysteine were added to dimethyl sulfoxide solvent, stirred and dispersed, nitrogen was introduced for protection, and the reaction was carried out at 70° C. for 4 h, and then 400 W / m 2 UV irradiation, after the reaction is completed, the solvent is removed by vacuum rotary evaporation to obtain L-cysteine modified carbon nanotubes;
[0037] (6) adding quaternized adamantane and L-cysteine modified carbon nanotubes to N,N-dimethylformamide solvent, stirring and mixing, adding pyridine catalyst, wherein the mass ratio of quaternized adamantane, L-cysteine modified carbon nanotubes, and pyridine catalyst is 1:1.5:0.03, reacting at 90° C. for 13 h, and then distilling under reduced pressure, filtering and drying to obtain adamantane modified carbon nanotubes;
[0038] (7) 12 parts by weight of adamantane-modified phenolic resin, 8 parts by weight of adamantane-modified carbon nanotubes, 3 parts by weight of talc, 0.9 parts by weight of film-forming aid propylene glycol, and 0.3 parts by weight of defoaming agent BYK088 were added to a high-speed mixer and mixed for 10 minutes. The mixture was then sent to a screw extruder for melt extrusion. The temperature of the feeding section was 45° C., the temperature of the melting section was 110° C., and the temperature of the discharging section was 170° C. The molten material was tableted by a tablet press with a thickness of 5 mm. The molten material was crushed and sent to a grinding mill for pulverization and classification. The fine powder and impurities were separated by a cyclone separator, and the product was separated by a powder sieve to obtain a halogen-free flame-retardant solid powder coating.
[0039] Example 3
[0040] (1) adding phenol, an aqueous solution of formaldehyde, and oxalic acid into a three-necked flask, reacting at 70° C. for 3 h, and then continuously adding cardanol thereto, wherein the mass ratio of phenol, the aqueous solution of formaldehyde, oxalic acid, and cardanol is 2.35:1:0.5:0.8, and continuing the reaction for 4 h. After the reaction is completed, washing with deionized water and standing for 20 h, after the reaction is completed, filtering and washing to obtain a cardanol-modified phenolic resin;
[0041] (2) adding 3-hydroxy-1-methacryloyloxyadamantane and hexamethyldisilazane to N,N-dimethylformamide solvent, stirring and dissolving, and continuously adding chloroplatinic acid catalyst thereto, wherein the mass ratio of 3-hydroxy-1-methacryloyloxyadamantane, hexamethyldisilazane, and chloroplatinic acid catalyst is 1:1.3:0.02, reacting at 82.5° C. for 6 h, and then performing reduced pressure distillation after completion, washing, and drying to obtain tertiary amine adamantane;
[0042] (3) adding tertiary amine adamantane and p-chloromethylbenzoyl chloride to N,N-dimethylformamide solvent, wherein the mass ratio of tertiary amine adamantane to p-chloromethylbenzoyl chloride is 1.3:1, introducing nitrogen protection, reacting at 80° C. for 9 h, and then rotary distilling and washing to obtain quaternary ammonium adamantane;
[0043] (4) adding dichloromethane solvent, quaternized adamantane, cardanol-modified phenolic resin, and triethylamine catalyst into a reactor, wherein the mass ratio of quaternized adamantane, cardanol-modified phenolic resin, and triethylamine catalyst is 1.55:1:0.03, reacting at 40° C. for 11 h, separating by column chromatography after the reaction, and washing with petroleum ether to obtain adamantane-modified phenolic resin;
[0044] (5) 6.5 parts by weight of vinyl carbon nanotubes and 8 parts by weight of L-cysteine were added to dimethyl sulfoxide solvent, stirred and dispersed, nitrogen was introduced for protection, and the reaction was carried out at 65° C. for 3 h, and then 360 W / m 2 UV irradiation, after the reaction is completed, the solvent is removed by vacuum rotary evaporation to obtain L-cysteine modified carbon nanotubes;
[0045] (6) adding quaternized adamantane and L-cysteine modified carbon nanotubes to N,N-dimethylformamide solvent, stirring and mixing, adding pyridine catalyst, wherein the mass ratio of quaternized adamantane, L-cysteine modified carbon nanotubes, and pyridine catalyst is 1:1.15:0.02, reacting at 82° C. for 11.5 h, and then distilling under reduced pressure, filtering and drying to obtain adamantane modified carbon nanotubes;
[0046] (7) 9 parts by weight of adamantane-modified phenolic resin, 6.5 parts by weight of adamantane-modified carbon nanotubes, 2 parts by weight of talc, 0.75 parts by weight of film-forming aid propylene glycol, and 0.25 parts by weight of defoaming agent BYK088 were added to a high-speed mixer and mixed for 8 minutes. The mixture was then sent to a screw extruder for melt extrusion. The temperature of the feeding section was 37° C., the temperature of the melting section was 95° C., and the temperature of the discharging section was 140° C. The molten material was pressed into tablets by a tablet press to control the thickness to be 3.5 mm. The molten material was then crushed and sent to a grinder for pulverization and classification. The fine powder and impurities were separated by a cyclone separator, and the product was separated by a powder sieve to obtain a halogen-free flame-retardant solid powder coating.
[0047] Comparative Example 1
[0048] (1) adding phenol, an aqueous solution of formaldehyde, and oxalic acid into a three-necked flask, reacting at 70° C. for 3 h, and then continuously adding cardanol thereto, wherein the mass ratio of phenol, the aqueous solution of formaldehyde, oxalic acid, and cardanol is 2.35:1:0.5:0.8, and continuing the reaction for 4 h. After the reaction is completed, washing with deionized water and standing for 20 h, after the reaction is completed, filtering and washing to obtain a cardanol-modified phenolic resin;
[0049] (2) adding 3-hydroxy-1-methacryloyloxyadamantane and hexamethyldisilazane to N,N-dimethylformamide solvent, stirring and dissolving, and continuously adding chloroplatinic acid catalyst thereto, wherein the mass ratio of 3-hydroxy-1-methacryloyloxyadamantane, hexamethyldisilazane, and chloroplatinic acid catalyst is 1:1.3:0.02, reacting at 82.5° C. for 6 h, and then performing reduced pressure distillation after completion, washing, and drying to obtain tertiary amine adamantane;
[0050] (3) adding tertiary amine adamantane and p-chloromethylbenzoyl chloride to N,N-dimethylformamide solvent, wherein the mass ratio of tertiary amine adamantane to p-chloromethylbenzoyl chloride is 1.3:1, introducing nitrogen protection, reacting at 80° C. for 9 h, and then rotary distilling and washing to obtain quaternary ammonium adamantane;
[0051] (4) adding dichloromethane solvent, quaternized adamantane, cardanol-modified phenolic resin, and triethylamine catalyst into a reactor, wherein the mass ratio of quaternized adamantane, cardanol-modified phenolic resin, and triethylamine catalyst is 1.55:1:0.03, reacting at 40° C. for 11 h, separating by column chromatography after the reaction, and washing with petroleum ether to obtain adamantane-modified phenolic resin;
[0052] (5) 9 parts by weight of adamantane-modified phenolic resin, 2 parts by weight of talc, 0.75 parts by weight of film-forming aid propylene glycol, and 0.25 parts by weight of defoamer BYK088 were added to a high-speed mixer and mixed for 8 minutes. The mixture was then sent to a screw extruder for melt extrusion. The temperature of the feeding section was 37° C., the temperature of the melting section was 95° C., and the temperature of the discharging section was 140° C. The molten material was tableted by a tablet press with a thickness of 3.5 mm. The molten material was crushed and sent to a grinder for pulverization and classification. The fine powder and impurities were separated by a cyclone separator, and the product was separated by a powder sieve to obtain a halogen-free flame-retardant solid powder coating.
[0053] Comparative Example 2
[0054] (1) 6.5 parts by weight of vinyl carbon nanotubes and 8 parts by weight of L-cysteine were added to a dimethyl sulfoxide solvent, stirred and dispersed, nitrogen was introduced for protection, and the reaction was carried out at 65° C. for 3 h, and then 360 W / m 2 UV irradiation, after the reaction is completed, the solvent is removed by vacuum rotary evaporation to obtain L-cysteine modified carbon nanotubes;
[0055] (2) adding quaternary ammonium adamantane and L-cysteine modified carbon nanotubes to N,N-dimethylformamide solvent, stirring and mixing, adding pyridine catalyst, wherein the mass ratio of quaternary ammonium adamantane, L-cysteine modified carbon nanotubes, and pyridine catalyst is 1:1.15:0.02, reacting at 82° C. for 11.5 h, and then distilling under reduced pressure, filtering and drying to obtain adamantane modified carbon nanotubes;
[0056] (3) 6.5 parts by weight of adamantane-modified carbon nanotubes, 2 parts by weight of talc, 0.75 parts by weight of film-forming aid propylene glycol, and 0.25 parts by weight of defoaming agent BYK088 were added to a high-speed mixer and mixed for 8 minutes. The mixture was then sent to a screw extruder for melt extrusion. The temperature of the feeding section was 37°C, the temperature of the melting section was 95°C, and the temperature of the discharging section was 140°C. The molten material was pressed into tablets by a tablet press with a thickness of 3.5 mm. The tablets were crushed and sent to a grinder for pulverization and classification. The fine powder and impurities were separated by a cyclone separator, and the product was separated by a powder sieve to obtain a halogen-free flame-retardant solid powder coating.
[0057] The limiting oxygen index of water-based paint was tested using an oxygen index meter; the combustion level of water-based paint was tested using a horizontal and vertical combustion instrument. The test results are shown in Table 1.
[0058] Table 1: Flame retardancy tests.
[0059]
[0060]
[0061] It can be seen from Table 1 that the halogen-free flame retardant solid powder coatings prepared in Examples 1-3 of the present invention have better flame retardant effects than those prepared in Comparative Examples 1-2.
[0062] Staphylococcus aureus was inoculated into beef extract peptone for culture activation, and then the activated Staphylococcus aureus suspension was added to a sterile culture dish, and culture medium and phosphate buffer solution were added, and cultured at a constant temperature of 37°C for 24 hours, and the halogen-free flame retardant solid powder coating prepared in Example 1-3 and Comparative Example 1-2 was added. After culture, the antibacterial rate was calculated, and the test results are shown in Table 2.
[0063] Table 2: Antimicrobial testing.
[0064] project Antibacterial rate (%) Example 1 99.5 Example 2 99.8 Example 3 99.7 Comparative Example 1 74.1 Comparative Example 2 73.5
[0065] It can be seen from Table 2 that the halogen-free flame retardant solid powder coatings prepared in the present invention, Examples 1-3 have better antibacterial effects than Comparative Examples 1-2.
[0066] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A process for preparing a halogen-free flame retardant solid powder coating, characterized in that: The preparation process of the halogen-free flame retardant solid powder coating comprises the following steps: (1) adding an aqueous solution of phenol and formaldehyde and oxalic acid into a three-necked flask, reacting at 60-80° C. for 2-4 hours, then adding cardanol thereto, continuing the reaction for 3-5 hours, washing with deionized water after the reaction, standing for 16-24 hours, filtering and washing after the reaction, and obtaining a cardanol-modified phenolic resin; (2) adding 3-hydroxy-1-methacryloyloxyadamantane and hexamethyldisilazane to N,N-dimethylformamide solvent, stirring and dissolving, adding chloroplatinic acid catalyst thereto, reacting at 75-90° C. for 4-8 hours, and then performing reduced pressure distillation, washing and drying to obtain tertiary amine adamantane; (3) adding tertiary amine adamantane and p-chloromethylbenzoyl chloride to N,N-dimethylformamide solvent, introducing nitrogen protection, reacting at 70-90° C. for 8-10 hours, and then performing rotary distillation and washing to obtain quaternary ammonium adamantane; (4) adding dichloromethane solvent, quaternized adamantane, cardanol-modified phenolic resin, and triethylamine catalyst to a reactor, reacting at 30-50° C. for 8-14 hours, separating by column chromatography after the reaction, and washing with petroleum ether to obtain adamantane-modified phenolic resin; (5) Add 5-8 parts by weight of vinyl carbon nanotubes and 4-10 parts by weight of L-cysteine into dimethyl sulfoxide solvent, stir and disperse, introduce nitrogen protection, react at 55-70° C. for 2-4 hours, and then add 320-400 W / m 2 UV irradiation, after the reaction is completed, the solvent is removed by vacuum rotary evaporation to obtain L-cysteine modified carbon nanotubes; (6) adding quaternized adamantane and L-cysteine modified carbon nanotubes to N,N-dimethylformamide solvent, stirring and mixing, adding pyridine catalyst, reacting at 75-90° C. for 10-13 h, and then distilling under reduced pressure, filtering and drying to obtain adamantane modified carbon nanotubes; (7) 6-12 parts by weight of adamantane-modified phenolic resin, 5-8 parts by weight of adamantane-modified carbon nanotubes, 1-3 parts by weight of talc, 0.6-0.9 parts by weight of film-forming aid propylene glycol, and 0.2-0.3 parts by weight of defoamer BYK088 are added to a high-speed mixer and mixed for 6-10 minutes, and then sent to a screw extruder for melt extrusion. The temperature of the feeding section is 30-45°C, the temperature of the melting section is 80-110°C, and the temperature of the discharging section is 110-170°C. The molten material is pressed into tablets by a tablet press to control the thickness to be 2-5 mm, and then crushed and sent to a grinding mill for pulverization and classification. The fine powder and impurities are separated by a cyclone separator, and the product is separated by a powder sieve to obtain a halogen-free flame retardant solid powder coating.
2. The process for preparing the halogen-free flame retardant solid powder coating according to claim 1, characterized in that: The mass ratio of phenol, formaldehyde aqueous solution, oxalic acid and cardanol in (1) is 2.2-2.5:1:0.4-0.6:0.7-0.
9.
3. The preparation process of the halogen-free flame retardant solid powder coating according to claim 1, characterized in that: The mass ratio of 3-hydroxy-1-methacryloyloxyadamantane, hexamethyldisilazane and chloroplatinic acid catalyst in (2) is 1:1.2-1.4:0.01-0.
03.
4. The process for preparing the halogen-free flame retardant solid powder coating according to claim 1, characterized in that: The mass ratio of the tertiary amine adamantane to p-chloromethylbenzoyl chloride in (3) is 1.1-1.5:
1.
5. The process for preparing the halogen-free flame retardant solid powder coating according to claim 1, characterized in that: The mass ratio of quaternized adamantane, cardanol-modified phenolic resin and triethylamine catalyst in (4) is 1.4-1.7:1:0.02-0.
04.
6. The process for preparing the halogen-free flame retardant solid powder coating according to claim 1, characterized in that: The mass ratio of quaternized adamantane, L-cysteine modified carbon nanotubes and pyridine catalyst in (6) is 1:0.8-1.5:0.01-0.03.
Citation Information
Cited By
High-water-resistance and high-weather-resistance fluorocarbon paint and preparation method thereof
CN120349682A